DEVELOPMENT OF INSTRUMENT BASED ON WORDWALL APPLICATION FOR RIGHTS AND OBLIGATIONS TOPIC - Susilowati, Endang; Utaminingsih, Esty Setyo (Research and Development Journal of Education, 2024)
This study aims to increase students' understanding of implementing civic education and learning about the rights and obligations of grade IV elementary schools. This research is a type of R&D (Research and Development) development research using the 4D method; the subject of this study is the development of an evaluation instrument on the topic of rights and obligations for grade IV elementary school, which contains a grid of assessment instruments assisted by the Wordwall application with 20 questions in the form of 5 (five) double choice questions, short fills of 5 (five) items, 5 (five) points essay and match 5 (five) items. Three expert validators have tested this instrument of evaluation of rights and obligations to measure validity and reliability. From the results of the content validity test analysis, a value of 76 was obtained from the linguist validator, 96 from the material expert validator, and 88 from the media expert validator. After adding up the results of the three validators, they got a final score of 86.67, which is very high. The development of an evaluation instrument on rights and obligations for grade IV elementary school was declared very high and suitable for use.